2019
DOI: 10.18178/ijmmm.2019.7.4.452
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fillers and Processing Parameters on the Shrinkage of Injected Molding Polyamide 66

Abstract: The in-flow and cross-flow shrinkage of injected molding polyamide 66 (PA66) could be effectively reduced by optimizing glass fiber content and molding condition. The chosen molding conditions were melt temperature, cooling time and cooling temperature. The filler effect between glass fiber and clay on PA66 shrinkage also being compared. The result showed that glass fiber can effectively reduce the in-flow and cross-flow shrinkage by giving 54% to 86% reduction of shrinkage percentage. The optimum shrinkage wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Where, A, B, and C represent load, sliding velocity and sliding distance. Consequently, the response (i.e., minimum COF and SWR for GFRPA66 30 wt.% and GFRPA66 35 wt.% was calculated using Equations (3)–(6), respectively) [ 33 , 34 , 35 , 36 , 37 , 50 ]. (COF)GFRPA66 30 wt.% = +0.2866 + 0.0127 A+0.0196 B + 0.0130 C + 0.0238 AC + 0.0105 A 2 + 0.0105 B 2 − 0.0124 C 2 (COF)GFRPA66 35 wt.% = +0.2646 + 0.0613 A + 0.0524 B+0.0916 C + 0.0687AC + 0.0639B 2 − 0.0249 C 2 (SWR)GFRPA66 30 wt.% = +0.0142 − 0.0014 A + 0.0003 B − 0.0011 C − 0.0000 AB + 0.0000 C 2 (SWR)GFRPA6635 wt.% = +0.0186 − 0.0049B − 0.0056C + 0.0216 AB − 0.0205 AC − 0.0152BC + 0.0252 B 2 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Where, A, B, and C represent load, sliding velocity and sliding distance. Consequently, the response (i.e., minimum COF and SWR for GFRPA66 30 wt.% and GFRPA66 35 wt.% was calculated using Equations (3)–(6), respectively) [ 33 , 34 , 35 , 36 , 37 , 50 ]. (COF)GFRPA66 30 wt.% = +0.2866 + 0.0127 A+0.0196 B + 0.0130 C + 0.0238 AC + 0.0105 A 2 + 0.0105 B 2 − 0.0124 C 2 (COF)GFRPA66 35 wt.% = +0.2646 + 0.0613 A + 0.0524 B+0.0916 C + 0.0687AC + 0.0639B 2 − 0.0249 C 2 (SWR)GFRPA66 30 wt.% = +0.0142 − 0.0014 A + 0.0003 B − 0.0011 C − 0.0000 AB + 0.0000 C 2 (SWR)GFRPA6635 wt.% = +0.0186 − 0.0049B − 0.0056C + 0.0216 AB − 0.0205 AC − 0.0152BC + 0.0252 B 2 …”
Section: Resultsmentioning
confidence: 99%
“…To optimize the process variables for tribological performance, the central composite design (CCD) is used, and the results of the experiments are scientifically tabulated. The influence of process parameters of polyamide with varying weight percentages are identified and also the number of trials is reduced via RSM to improve the tribological performance [ 33 , 34 , 35 , 36 , 37 ]. Also, several related studies on the optimization of process variables using the RSM approach for improving the tribological performance in polyamide has been studied and adopted for the present work [ 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ].…”
Section: Introductionmentioning
confidence: 99%
“…Graphs were also drawn between the onset temperature of crystallisation and transverse mould direction shrinkage, with no statistically significant relationship being observed for the PP system. It has previously been reported that additives in semicrystalline polymers can effect shrinkage differently in the flow and crossflow direction [14,44,45]. Pulkerd et al reported that the outer skin layer of the injection moulded parts containing nucleating agents show orientation of crystals along the flow direction (MD) [46].…”
Section: Correlation Between Shrinkage and Onset Crystallisation Temp...mentioning
confidence: 99%